Orofacial, radiographic and salivary changes in thalassemia a major patients in Mosul (Mustansiria Dental Journal, 2024)
Thalassaemia is considered one of the major health problem, which is widely,distributed throughout the worldClinical orofacial, and radiographical examinations, in addition to the physicaland biochemical analysis of the whole unstimulated saliva had been studied in Majorthalassaemia patients (MTP) and the results compared with that of the normal.subjects)The study included (254) subjects. Thalassaemia patients (study groupcomposed of (201) patients and non-thalassaermic. patients (control group) composedof (53) subjects. Each group was divided into three subgroups according to their ages.and sex distribution to study the chronological changes ofthe diseaseThe first,second, and third groups were (6-11, 12-17,2 18) years old.respectivelyThe results of the study showed that, there was a significant difference in,occlusal relation between thalassaemie and non·thalassaemic groupsThalassaemic patients had a significant degree of malocclusion and high.significant degree of teeth discoloration than non-thalassaemie patientsThere were significant difference in oral hygein indices between thalassaemieand non-thalassaemie patients and even between male and female thalassaemie.patientsThe intraoral radiographical assessment of the major thalassaemie patientsshowed that, there was thinning of the lamina dura and bone marrow hyperplasia.which were significant when compaired with the non-thalassaemie patientsFacial pigmentation and saddle no se were highly significant in major.thalassaemie than non-thalassaemie patients